Evaluation of Housing of Low-in come Projectsin Ramadi City - sh. Mahmood, Thaer (Anbar Journal of Engineering Sciences, 2011)
The purposes of planning for housing and solve the housing problem of the most important topics in studies of housing also it is one of the topics broad and complex, and that the planned housing in accordance with the cost and social benefit is the solution to reduce the heights fantasy of the costs of housing. Also its negative effects on the process of housing where most of Iraq’s society of the middle class is needed to adequate housing with income, especially if we consider that there is a deficit of housing dramatically in Iraq. Which is estimated at more than three million housing units and offset by a significant decrease in the rates of housing construction, also which are led to the worsening problem of housing in the country, especially those with low income, so it requires the parties responsible speed up the adoption of the strategy to solve the problem of housing in the country adopt the principle of the establishment of residential low-cost through the adoption of residential buildings, multistorey (3-4) stories as characterized by the buildings of the densities of housing appropriate of effective use with economic land and reduce the costs of housing to meet the large deficit and demand residentialdemand. In order to reach the desired goal has been studied and the reality of the housing in Ramadi in the, Ta’meem, 5 km and the 7 km areas and limited the problems of constraints related with planning housing also its components as well as access to some of the experiences of countries in planning, housing and solving the housing crisis within finding the alternatives to some traditional building materials with finding teams cost whenusingthesealternatives. Also supports research field study of three residential compounds, which aims at evaluating the appropriateness of such style housing and how to achieve social benefits and meet the standards of planning and design proposed in the scheme of public housing in Iraq which have been using the method (analysis of cost - benefit) for the trade-off to choose the best alternative of residential complexes three (and low cost, Ta’meem, the 7 km), which achieves less expensive and better utility.